Flavonols as potent inhibitors of tyrosinase & pancreatic lipase: synthesis, docking, MD simulation, DFT, and ADMET - Mughal, Ehsan Ullah; Naeem, Nafeesa; Jabeen, Ayza; Alsantali, Reem I.; Shafiq, Nusrat; Shakoor, Bushra; Sadiq, Amina (Taylor & Francis Ltd, 2025)
AimsTyrosinase and pancreatic lipase are key enzymes involved in melanin biosynthesis and lipid metabolism, respectively. Their inhibition offers therapeutic potential in treating hyperpigmentation and obesity. This study aimed to synthesize and evaluate a series of flavonols (1-10) as potential dual enzyme inhibitors.Materials and MethodsTen flavonol derivatives were synthesized and structurally confirmed using spectroscopic techniques. Their inhibitory activities against tyrosinase and pancreatic lipase were assessed through in vitro enzyme assays. Molecular docking and molecular dynamics (MD) simulations were employed to explore binding modes and the stability of enzyme-ligand interactions. Density Functional Theory (DFT) calculations were performed to examine electronic features influencing binding affinity. Absorption, Distribution, Metabolism, Excretion, and Toxicity (ADMET) analysis was used to predict pharmacokinetic properties and drug-likeness.ResultsThe compounds exhibited variable inhibitory activity, with several showing significant dual inhibition. Docking and MD studies revealed stable binding within active sites, highlighting key interactions. DFT results supported structure-activity relationships by correlating electronic parameters with inhibitory potential. ADMET profiles were favorable for most derivatives.ConclusionsThis is the first study reporting pancreatic lipase inhibition by flavonols alongside their tyrosinase inhibitory potential. These flavonols emerge as promising dual-action candidates for developing treatments targeting obesity and hyperpigmentation.
Keywords: 3-Hydroxyflavones; tyrosinase; pancreatic lipase; SAR; docking; MD simulation; ADMET; DFT